Does Corporate Governance Have Implications for Firms: ASEAN Evidence - Goh, Chea Ei (2017)
This paper examines the impact of corporate governance on the cost of capital (COC), dividend policy and financial distress for a sample of companies in five ASEAN countries. The results indicate that insider ownership and CEO duality have positive influence on COC and a negative relationship between board independence and COC. Board size plays an important role in determining COC during financial crisis. Board independence is found to be significant in common law countries while board independence and insider ownership are significant variables in affecting COC in civil law countries. Moreover, the findings show that board independence, board size and insider ownership have positive impacts on dividend policy. Board size and blockholders shareholding are important to determine the dividends during financial crisis. Board independence, board size and insider ownership are found be to significant in civil law countries while board size, insider ownership and blockholders ownership are significant variables in affecting dividends in common law countries. Furthermore, CEO duality is important in affecting likelihood of financial distress especially during financial crisis and in civil law countries.